Mindreading abilities and borderline personality disorder: A comprehensive assessment using the Theory of Mind Assessment Scale. (February 2019) - Colle, L.; Gabbatore, I.; Riberi, E.; Borroz, E.; Bosco, F.M.; Keller, R.
Highlights: Mindreading impairment in individuals with borderline personality disorder (BPD). Th.o.m.a.s. interview allowed to assess different aspects of real-life mindreading. BPD performed worse than controls on allocentric perspective-taking. Mindreading functions as assessed by Th.o.m.a.s. correlates with depressive symptoms. Abstract: Numerous studies have examined mindreading in borderline personality disorder (BPD). However, the empirical data obtained to date have not facilitated the development of a clear clinical profile of mindreading impairment in BPD due to a lack of consistency or incongruence across studies. One possible explanation for these inconsistencies and divergences in the current literature may lie in the multidimensional character of the mindreading construct; moreover, the heterogeneity of the experimental measures used to assess individuals with BPD mindreading skills may also need to be taken into account. The aim of the present study is to investigate mindreading skills and impairments in patients with BPD through direct comparison of a wide range of mindreading dimensions using a comprehensive semistructured interview, the Theory of Mind Assessment Scale (Th.o.m.a.s.) (Bosco et al., 2009). Our results show that the performance of patients with BPD differs from that of healthy controls only in certain specific dimensions of mindreading. The difficulties encountered by the patients with BPD typically emerge when mindreading tasks require them to disentangle their own subjective mindreading from that of another person, in other words, when they were required to assume an allocentric perspective.